2012
DOI: 10.1104/pp.112.203075
|View full text |Cite
|
Sign up to set email alerts
|

A Chimeric Arabinogalactan Protein Promotes Somatic Embryogenesis in Cotton Cell Culture    

Abstract: Arabinogalactan proteins (AGPs) are a family of extracellular plant proteoglycans implicated in many aspects of plant growth and development, including in vitro somatic embryogenesis (SE). We found that specific AGPs were produced by cotton (Gossypium hirsutum) calli undergoing SE and that when these AGPs were isolated and incorporated into tissue culture medium, cotton SE was promoted. When the AGPs were partly or fully deglycosylated, SE-promoting activity was not diminished. Testing of AGPs separated by rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 80 publications
1
35
0
Order By: Relevance
“…As shown in Fig. 2A, characteristic AGP-like smeared bands in a high molecular weight range were observed on respective SDS/PAGE gels stained with either Coomassie brilliant blue or 0.2% (wt/vol) β-GlcY dye (35,36). Consistent with the gel information, the presence of AGPs in the purified ivy nanoparticles was further evidenced by Western blotting analysis using two mAbs, JIM13 and JIM14, which are commonly used to specifically recognize glycan epitopes of typical AGPs (see Table S1), as shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…As shown in Fig. 2A, characteristic AGP-like smeared bands in a high molecular weight range were observed on respective SDS/PAGE gels stained with either Coomassie brilliant blue or 0.2% (wt/vol) β-GlcY dye (35,36). Consistent with the gel information, the presence of AGPs in the purified ivy nanoparticles was further evidenced by Western blotting analysis using two mAbs, JIM13 and JIM14, which are commonly used to specifically recognize glycan epitopes of typical AGPs (see Table S1), as shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…To test whether AGPs are contained in the ivy nanoparticles, Yariv phenylglycoside dye, a reagent also called β-glucosyl Yariv (β-GlcY), which selectively binds to the AGPs via recognizing both given protein moieties and β-1,3-galactan chains with greater than five residues (24,30,(32)(33)(34)(35), was applied for identification. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Poon et al found that some specific Arabinogalactan proteins were isolated and incorporated into tissue culture medium, cotton somatic embryogenesis can be promoted [26]. This also indicated that exogenous proteins can be transformed into plant cells and play roles directly.…”
Section: Discussionmentioning
confidence: 94%
“…In the plant model Gossypium hirsutum the increased rate of somatic embryos induction was statistically greater with the inclusion of the extracellular AGPs fraction into the culture medium (Poon et al 2012). Furthermore, it is known that a specific set of AGPs could have an inhibitory effect on somatic embryogenesis ) as has been documented with AGPs extracted from G. hirsutum non-embryogenic calli, which inhibited somatic embryogenesis when incorporated into the culture media of the same species (Poon et al 2012).…”
Section: 1 Arabinogalactan Proteins and Pectinsmentioning
confidence: 94%